(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
This article focuses on the Mapudungún segmental phonology in general, and the status of the interdental phones [t°], [n°] and [l°] from the Chedungun spoken in Alto Biobío in particular. An adapted lexicon list by Croese (1980) was elicited from 30 adult bilingual assistants (Chedungun and Spanish speakers), belonging to 10 towns of this community (three from each one). Through the quantitative, visual, palatographic and analog environment contrast we concluded that those phones have phonemic status in the mentioned area.